Поняття короткочасних виїздів засуджених в Україні за межі колонії - Колб, О.; Крук, O.; Kolb, А.; Kruk, О. (Східноєвропейський національний університет імені Лесі Українки, 2015)
В статті здійснений аналіз наукових розробок з питань, що стосуються застосування в Україні короткострокових виїздів засуджених за межі колоній, на підставі якого визначені теоретико-прикладні проблеми, що потребують вирішення по суті та обумовлюють необхідність більш активної їх розробки на рівні монографічних і дисертаційних досліджень. One of the institutions of criminal executive law, which can influence condemned to imprisonment positively, stimulate their law-obedience and correction, is short-term departures of convicts from colonies. Now the right of condemned to imprisonment to leave the place of imprisonment is connected with a number of theoretical as well as practical questions. There is no complex conception of the content of this institution, reasons for implementation and the procedure of these departures are investigated and regulated in normative legal acts insufficiently. This situation is the result of insufficient attention of scientific community in particular. The conclusion has been made that the distinguishing in the Criminal Executive Code of Ukraine of short-term departures is inappropriate due to the fact that long-term kinds of departures do not exist. To eliminate the mentioned flaw it is necessary to change the title of the article 111 of the Criminal Executive Code of Ukraine and edit it in the following way: “Departures of convicts from establishments of execution of punishment”. Such a version was fixed in Model criminal executive code for member countries of CIS, approved by the resolution of Inter-parliamentary Assembly of participating countries of CIS from 2 November 1996, some principles of which were reflected in the Criminal Executive Code of Ukraine. The authors of the article have formulated a general definition of a convict’s departure from colonies as a convict’s temporary (limited by a definite period) departure from the establishment of execution of punishment on the grounds and in order defined in law to support family relations, receive medical help, and solve other questions connected with resocialization of a person.
Concept of short-term departures of convicts from a colony in Ukraine
Keywords: засуджений; колонія; позбавлення волі; короткостроковий виїзд за межі колонії; адміністрація колонії; правові підстави; фактичні підстави; правові наслідки; виняткові обставини; convict; colony; imprisonment; short-term departure from a colony; administration of a colony